Curcumin analog GO‐Y030 boosts the efficacy of anti‐PD‐1 cancer immunotherapy. Issue 12 (19th October 2021) - MaruYama, Takashi; Kobayashi, Shuhei; Shibata, Hiroyuki; Chen, WanJun; Owada, Yuji
Abstract: Regulatory T cells (Tregs) in the tumor microenvironment regulate tumor immunity. Programmed cell death protein 1 (PD‐1) is known to be expressed on Tregs and plays crucial roles in suppressing tumor immunity. However, the immune checkpoint inhibitor, anti‐PD‐1 antibody, is known to promote the proliferation of the Treg population in tumor‐infiltrating lymphocytes, thereby restricting the efficacy of cancer immunotherapy. In this study, we focused on the curcumin analog GO‐Y030, an antitumor chemical. GO‐Y030 inhibited the immune‐suppressive ability of Tregs via metabolic changes in vitro, even in the presence of immune checkpoint inhibitors. Mechanistically, GO‐Y030 inhibited the mTOR‐S6 axis in Tregs, which plays a pivotal role in their immune‐suppressive ability. GO‐Y030 also controlled the metabolism in cultured CD4 + T cells in the presence of TGF‐β + IL‐6; however, it did not prevent Th17 differentiation. Notably, GO‐Y030 significantly inhibited IL‐10 production from Th17 cells. In the tumor microenvironment, L‐lactate produced by tumors is known to support the suppressive ability of Tregs, and GO‐Y030 treatment inhibited L‐lactate production via metabolic changes. In addition, experiments in the B16‐F10 melanoma mouse model revealed that GO‐Y030 helped inhibit the anti‐PD‐1 immune checkpoint and reduce the Treg population in tumor‐infiltrating lymphocytes. Thus, GO‐Y030 controls the metabolism of both Tregs and tumors and could serve as a booster for anti‐immune checkpoint inhibitors. Abstract : Curcumin analog GO‐Y030 boosts cancer immunotherapy via metabolic changes.